Stories of Becoming : Demystifying the Professoriate for Graduate Students in Composition and Rhetoric - Lutkewitte, Claire; Scanlon, Molly J.; Kitchens, Juliette C., 1976- (Book collections on Project MUSE., 2021)
"Findings from a multiyear, nationwide study of new faculty in rhetoric and composition, provides graduate students--and those who train them--strategies for career preparation. Through the use of stories, invite readers to experience their collaborative research for conducting a nationwide survey, qualitative interviews, and textual analysis of documents"--